« Napguana (Terre-Mère) vs. Bab Dummat (Père Créateur). Les représentations kunas de l’environnement dans les espaces de médiation ». - Mònica Martínez Mauri (Nuevo mundo - Mundos Nuevos, 2007)
Napguana (Mother Earth) vs. Bab Dummat (Great Father). Kuna representations of the environment in spaces of mediation.Although for the inhabitants of Kuna Yala the sea and the land are two constitutive elements of the environment, for the Kunas who participe in international fora on indigenous issues the Mother-Earth has become the single most important point of reference when it comes to represent the indigenous physical and spiritual world to outsiders. Through speeches of Kuna NGOs members and local representations of the environment in the transnational spaces, this paper reflects on the feelings of belonging with respect to Kuna territory in Kuna Yala.